Impact of Coupled Resonator Geometry on Silicon-on Insulator Wavelength Filter Characteristics - Mardiana, Bidin; Hazura, Haroon; Hanim, Abdul Razak; zulatfyi, F. Mohamed Hanapiah (IEEEXplore, 2011)
We have analyzed and discussed the issues arising in the design of Silicon - on - Insulator (SOI) wavelength filters with different types of device geometry. Microring and microdisk geometries have been chosen as the device configurations and in order to demonstrate the device performance and potential, Free Spectral Range (FSR), and Q-factor values are computed. Studies of the transmittance characteristics are carried out using Finite- Difference Time-Domain (FDTD) methods by RSOFT Software. Results show that the microring-based wavelength filter has a FSR of 1.4 THz and a Q-factor value of 486. On the other hand,the microdisk based filter has a broader FSR with slightly smaller Q-factor.